2021
DOI: 10.1002/biof.1808
|View full text |Cite
|
Sign up to set email alerts
|

Ginger and its constituents: Role in treatment of inflammatory bowel disease

Abstract: Inflammatory bowel diseases (IBD), with obscure etiology, are rising and are of worldwide concern. Of the various components of IBD pathogenesis and progression, irritation appears to play a major part. Investigations on the molecular and cellular pathways that activate the IBD provide the focus for the development of useful therapies. Ginger (the rhizome of Zingiber officinale) has a broad spectrum of clinical applications due to its anti‐inflammatory and anti‐oxidative functions. Inflammation and oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 71 publications
(189 reference statements)
0
24
0
1
Order By: Relevance
“…When inflammation occurs, TLR4 is activated, which activates the NF-κB transcription factor via inflammatory signaling pathways that play an essential role in triggering and promoting IBD [27]. Previous studies have shown that IBD-induced inflammation can be alleviated by inhibiting the TLR4 receptor and NF-κB signaling pathway [33,34]. Thus, inhibition of the TLR4/NF-κB signaling pathway can be considered one of the new approaches to treating IBD [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…When inflammation occurs, TLR4 is activated, which activates the NF-κB transcription factor via inflammatory signaling pathways that play an essential role in triggering and promoting IBD [27]. Previous studies have shown that IBD-induced inflammation can be alleviated by inhibiting the TLR4 receptor and NF-κB signaling pathway [33,34]. Thus, inhibition of the TLR4/NF-κB signaling pathway can be considered one of the new approaches to treating IBD [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…It has been known as a folk medicine for thousands of years. Some regulatory authorities classify ginger as a safe herbal supplement ( Vemuri et al, 2017 ), and it has been used both in complementary and alternative medicine preparations for the management of fevers, colds, and headaches, as an appetite stimulant, antibacterial, antiviral, antidiarrheal, choleretic, anti-emetic, and expectorant, to name a few ( Dugasani et al, 2010 ; Embuscado, 2015 ; Konmun et al, 2017 ; de Menezes de Lima et al, 2018 ; Liang et al, 2018 ; Lashgari et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on ginger extracts and the phenolic compounds isolated from them, showing that gingerols have various pharmacological effects, mainly 6-gingerol. These include antiemetic, anti-inflammatory, antinociceptive, antioxidant, antimicrobial, anti-cancer, anti-hyperglycemic, anti-arteriosclerotic, rubefacient, digestive, and laxative effects ( Semwal et al, 2015 ; Hitomi et al, 2017 ; Samad et al, 2017 ; Wang et al, 2018a ; Ghasemzadeh et al, 2018 ; Han et al, 2018 ; Ho and Chang, 2018 ; Lee et al, 2018 ; Smith et al, 2018 ; Han et al, 2022a ; Lashgari et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some plants have medicinal properties that have led them to be used to manufacture NPs. Various plants, including Aloevera, Punica granatum, and Allium sativum, have been used to synthesize CuNPs [23,24].…”
Section: Introductionmentioning
confidence: 99%